Impact of Feeding Frequency on Growth Performance and Antioxidant Capacity of Litopenaeus vannamei in Recirculating Aquaculture Systems - Qinlang Liang; Gang Liu; Yazhi Luan; Jiangbo Niu; Yasong Li; Huwei Chen; Ying Liu; Songming Zhu (Animals)
Feeding frequency is crucial for the growth and development of white shrimp (Litopenaeus vannamei) at various life stages. Although higher feeding frequencies can enhance growth, manual feeding methods significantly increase labor costs. Automatic feeding systems offer a cost-effective and efficient alternative, yet their application in intensive shrimp culture remains under-researched. This study evaluates different feeding frequencies for L. vannamei in intensive aquaculture tanks, focusing on growth performance, survivability, feed utilization, digestive and antioxidant capacities, and economic viability. Juvenile shrimp (3.85 ± 0.3 g) were cultured for 63 days with feeding frequencies of 6, 8, 10, and 12 times/day (A6, A8, A10, and A12 groups, respectively) using automatic feeders, with a control group fed manually 6 times/day (M6). Results indicated that automatic feeding significantly improved final body weight, specific growth rate, and feed conversion ratio compared to manual feeding. Among automatic feeding groups, A6 and A8 showed optimal performance, with a quadratic regression identifying 7.83 times/day as the optimal frequency. While digestive enzyme activity remained consistent across groups, A6 and A8 demonstrated significantly higher antioxidant enzyme levels (superoxide dismutase (SOD) and glutathione peroxidase (GPx)) and lower lipid peroxidation (MDA), suggesting superior digestive and antioxidant capacities. Pearson’s correlation confirmed a positive relationship between SOD and GPx. Economically, the A8 group achieved the highest profitability. Consequently, a feeding frequency of 6–8 times/day using automatic feeders is recommended as an optimal and feasible strategy for intensive white shrimp culture in this life stage.